Crop loading studies on ‘Caricia’ and ‘Eva’ apples grown in a mild winter area (Scientia Agricola, 2015)
The crop load level of an apple (Malus × domestica Borkh.) tree impacts fruit yield and quality parameters, tree vigor and biennial bearing. The optimal crop load is that which allows for consistent annual cropping and fruit quality acceptable to the market. We evaluated the effect of crop load on yield and fruit quality of two low-chill apples cv. ‘Caricia’ and ‘Eva’, growing in a mild winter area. During 2010 and 2011 crop load was manually adjusted from 2 or 3 to 17 fruits cm−2 of trunk cross-sectional area (TCSA). Fruit yield was positively related to crop load in both cultivars but mean fruit weight diminished as the crop load increased. For both cultivars, the production of non-commercial and small-sized fruit increased, whereas production of middle-sized fruit diminished as the fruit load increased. Shoot length was not affected by crop load in ‘Eva’ whereas it was reduced in ‘Caricia’. Red skin color (RSC %) had a quadratic response to crop load in ‘Caricia’. On the other hand, the RSC % of ‘Eva’ fruit was adjusted to a negative logarithmic model as an effect of crop load increment. No biennial bearing was observed in either cultivar. This research study suggests that the maximum limit of crop load for both cultivars is 7 fruits cm−2 of TCSA, and the lower limit of crop load was 3 fruits cm−2 of TCSA for ‘Eva’ and 5 fruits cm−2 of TCSA for ‘Caricia’.